2000
DOI: 10.1177/001440290006700106
|View full text |Cite
|
Sign up to set email alerts
|

Key Influences on the Initiation and Implementation of Inclusive Preschool Programs

Abstract: Inclusion is a challenging educational practice to implement at the preschool level. We interviewed early childhood teachers, related services providers, program directors, and state-level administrators in 18 public schools, Head Start, and community-based programs in four geographical regions across the United States. Interviews were analyzed to determine factors that were facilitators of or barriers to the development of inclusive preschool programs and to describe where inclusion began for each of the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 13 publications
2
37
0
Order By: Relevance
“…Classroom quality, however, is an important consideration when deciding whether to place a child with disabilities in a class (Bailey, McWilliam, Buysse, & Wesley, 1998;Odom, 2000). Another central issue is the nature and amount of supports available to the teachers in the class (Lieber et al, 2000;Scruggs & Mastropieri, 1996). Classroom quality and staff supports potentially influence whether important goals can be taught in inclusive classes and more specifically whether individualized and specialized intervention practices are used.…”
Section: Vanderbilt Universitymentioning
confidence: 99%
“…Classroom quality, however, is an important consideration when deciding whether to place a child with disabilities in a class (Bailey, McWilliam, Buysse, & Wesley, 1998;Odom, 2000). Another central issue is the nature and amount of supports available to the teachers in the class (Lieber et al, 2000;Scruggs & Mastropieri, 1996). Classroom quality and staff supports potentially influence whether important goals can be taught in inclusive classes and more specifically whether individualized and specialized intervention practices are used.…”
Section: Vanderbilt Universitymentioning
confidence: 99%
“…The building blocks model emphasises that a high-quality early childhood learning environment is the foundation for successful inclusion. Literature on preschool inclusion widely supports the belief that high quality early childhood programmes set a solid foundation for successful inclusive practices (Buysse, Wesley, and Keyes 1998;Cross et al 2004;Diamond and Carpenter 2000;Lieber et al 2000). Additionally, research that compared the overall quality of inclusive programmes and non-inclusive programmes, found that inclusive preschools tended to score higher on overall quality (Buysse et al 1999;Hestenes, Cassidy, and Hedge 2004).…”
Section: Development Of Preschool Inclusion In Beijingmentioning
confidence: 96%
“…The substantive statements identified in the transcripts were coded using tbe previously developed Lieber et al (2000) and rwo additional factors-collaborative relationship and family as initiator/family support and partnershipthat emerged during the data analysis process (see Table 3 for a listing of all eight key factors). As noted, individual case reports were developed for each site.…”
Section: Resu Ltsmentioning
confidence: 99%